How Live Music Can Be Delivered to Children and Young People to Support Their Mental Health and Wellbeing: Co-Produced Solutions and Key Findings from a Series of Intergenerational Multi-Disciplinary Workshops - Lynne Gilmour; Louise Honeybul; David Mackay; Jenny Jamison; Amy Woodhouse (Youth)
Background: Children and young people’s (CYP) mental health is a policy priority, with rates of poor mental health reported to be as much as one in five across the UK. Traditional mental health support services cannot meet demand, and new approaches are needed. The creative arts can be an effective tool in supporting mental health. However, little is known about how live music can be used to support CYP mental health and wellbeing. We facilitated three, two-day intergenerational and multi-disciplinary workshops to co-produce ideas about how live music could be delivered to this end. Results: Workshops were held in three locations in Scotland, attended by a mixture of CYP, youth workers, mental health practitioners, teachers, and musicians (n = 91). A range of co-created solutions were generated including a live music festival designed for and with CYP and free gig tickets. Barriers and facilitators for CYP accessing live music were also identified. Furthermore, these workshops were found to increase confidence for musicians in delivering live music events to CYP, and CYP felt their voices were heard in their design of the delivery. Conclusions: This study presents novel co-created solutions about how live music can be delivered to CYP that need to be tried and tested in future research. It also provides key insights for musicians, live music providers, and people supporting CYP about the best approach to delivering live music for CYP.